In-vitro Anthelmintic activity of leaf extracts of Shorea tumbuggaia Roxb. and Holostemma ada Kodien Schult. on (Pheretima posthuma )Indian earthworm. - SADASIVAM, RUBESH KUMAR; SRIDHAR, CHENCHUGARI; JAYAVEERA, KORLAKUNTA NARASIMHA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The present study was undertaken to evaluate anthelmintic activity for the leaf extracts of two folk medicinal plants from the southern Eastern Ghats of India; Shorea tumbuggaia Roxb. (Dipterocarpaceae) and Holostemma ada Kodien Schult (Asclepiadaceae) were used for it various properties for the cure of aliments related to natural causes. Methanolic and hydroalcoholic (S. tumbuggaia Roxb.) extracts and methanolic and ethyl acetate (H. ada K. Schult.) extracts were determined for the anthelmintic activity. The phytochemical investigation reveals the presence of tannins, flavonoids, saponins, terpenoids steroids, anthocyanins glycoside and reducing sugars were the major phytoconstitution presence in the extracts. Â In-vitro anthelmintic studies was carried out using Pheretima posthuma (Indian earth worm) as test worms, various concentrations (50, 100, 200 and 400 Âµg/ml) of extract, were tested in the bioassay, which involved determination of time of paralysis (P) and time of death (D) of the worms. Albendazole was used as standard reference and distilled water as control. The paralytic action and death rate of both plant extract for the methanolic extracts and ethyl acetate extract were found to be exhibits the anthelmintic activity. Â Further studies to be conducted for the isolation of bioactive principle/s responsible for the activity.